Ecosystem carbon stock and annual sequestration rate from three genera-dominated mangrove zones in Benoa Bay, Bali, Indonesia - I PUTU SUGIANA; TRI PRARTONO; RASTINA RASTINA; ALAN FRENDY KOROPITAN (Society for Indonesian Biodiversity, 2024)
Abstract. Sugiana IP, Prartono T, Rastina, Koropitan AF. 2024. Ecosystem carbon stock and annual sequestration rate from three genera-dominated mangrove zones in Benoa Bay, Bali, Indonesia. Biodiversitas 25: 287-299. The mangrove ecosystem is an ecologically productive wetland system that serves as a carbon sink. However, various factors have contributed to the variation in values when calculating ecosystem carbon stock and the sequestration rate in the mangrove ecosystem. The presence of varying environmental conditions has resulted in the categorizing different species of mangroves, which may lead to variations in ecosystem carbon stock and sequestration rates. In this study, we aim to assess the ecosystem carbon stock and sequestration rate of the mangrove ecosystem in Benoa Bay, Bali, Indonesia. The ecosystem has been categorized into three zones based on the dominant genera: Bruguiera, Rhizophora, and Sonneratia. This research aimed to investigate the influence of mangrove zoning on the variability of carbon stock values and sequestration rates within the ecosystem. The allometric calculation technique and net primary productivity and soil organic carbon percentage values obtained using the Loss on Ignition (LOI) method are used to estimate each zone's ecosystem carbon stock and sequestration rate. The findings of our study indicate that there are notable variations in the carbon stock of ecosystems across different zones. However, we did not observe any substantial changes in the annual carbon sequestration rates. The Sonneratia zone exhibits the maximum value of ecosystem carbon stock and sequestration rate (1,570.9±248.0 tCO2ha-1 and 81.8 tCO2ha-1yr-1), while the Bruguiera zone demonstrates the lowest values (1,029.6±130.9 tCO2ha-1 and 75.6 tCO2ha-1yr-1). The three zones' average carbon stock and sequestration rate are estimated as 338.2 tCha-1 (1239.9 tCO2ha-1) and 21.5 tCha-1yr-1 (78.9 tCO2ha-1yr-1), respectively. In total, the carbon storage and absorption capacity of Benoa Bay amounts to 421,149 tC (equivalent to 1.5 million tCO2), with an annual rate of 25,769.4 tCyr-1 (equivalent to 94,573.6 tCO2yr-1). We recommended that future ecosystem carbon stock evaluations consider mangrove-type zoning characteristics due to significant value fluctuations in various mangrove zones found.